Physiological and Ecological Responses of Photosynthetic Processes to Oceanic Properties and Phytoplankton Communities in the Oligotrophic Western Pacific Ocean - Wei, Yuqiu; Chen, Zhuo; Guo, Congcong; Zhong, Qi; Wu, Chao; Sun, Jun (Frontiers in Microbiology, 2020)
Understanding the dynamics of primary productivity in a rapidly changing marine environment requires mechanistic insight into the photosynthetic processes (light absorption characteristics and electron transport) in response to the variability of environmental conditions and algal species. Here we examined the photosynthetic performance and related physiological and ecological responses to oceanic properties (temperature, salinity, light, size-fractionated chlorophyll a (Chl a) and nutrients) and phytoplankton communities in the oligotrophic Western Pacific Ocean (WPO). Our results revealed high variability in the maximum (Fv/Fm; 0.08-0.26) and effective (Fq'/Fm'; 0.02-0.22) photochemical efficiency, the efficiency of charge separation (Fq'/Fv'; 0.19-1.06), the photosynthetic electron transfer rates (ETRRCII; 0.02-5.89 mol e- mol RCII-1 s-1 ) and the maximum of primary production (PPmax; 0.04-8.59 mg C (mg chl a)-1 h-1). All these photosynthetic characteristics showed a depth-specific dependency based on respective nonlinear regression models. On physiological scales, variability in light absorption parameters Fv/Fm and Fq'/Fm' notably correlated with light availability and size-fractionated Chl a, while both ETRRCII and PPmax were correlated to temperature, light and ambient nutrient concentration. Since the presence of non-photochemical quenching (NPQNSV; 2.33-12.31) and increasing reductant used for functions other than carbon fixation, we observed nonparallel changes in the ETRRCII and Fv/Fm, Fq'/Fm', Fq'/Fv'. In addition, we found that the important biotic variables influencing Fv/Fm were diatoms (cells >2 µm), pico-sized Prochlorococcus and eukaryotes, but the PPmax was closely related to large cyanobacteria (cells >2 µm), dinoflagellates and pico-sized Synechococcus. The implication is that, on ecological scales, an interaction among temperature, light and nutrient availability may be key in driving the dynamics of primary productivity in the WPO, while large cyanobacteria, dinoflagellates and pico-sized Synechococcus may have a high contribution to the primary production. Overall, the photosynthetic processes are interactively affected by complex abiotic and biotic variables in marine ecosystems, rather than by a single variable.